2023
DOI: 10.1038/s41477-023-01482-1
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical assessment of persistence and adaptation in weeds with complex life cycles

Abstract: Herbicide-resistant weeds pose a substantial threat to global food security. Perennial weed species are particularly troublesome. Such perennials as Sorghum halepense spread quickly and are difficult to manage due to their ability to reproduce sexually via seeds and asexually through rhizomes. Our theoretical study of S. halepense incorporates this complex life cycle with control measures of herbicide application and tillage. Rooted in the biology and experimental data of S. halepense, our population-based mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Seed banks preserve genetic information of forgone selection for resistance and prolong the period in which a weed can adapt towards a herbicide, emphasising the complications seed banks impose on managing herbicide resistance. A previous study showed that a seed bank substantially delays the extinction of a herbicide-treated weed population and increases the risk of resistance (Lauenroth and Gokhale, 2023). Further, a seed bank buffers the genetic effects of selection, slowing resistance evolution if it occurs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Seed banks preserve genetic information of forgone selection for resistance and prolong the period in which a weed can adapt towards a herbicide, emphasising the complications seed banks impose on managing herbicide resistance. A previous study showed that a seed bank substantially delays the extinction of a herbicide-treated weed population and increases the risk of resistance (Lauenroth and Gokhale, 2023). Further, a seed bank buffers the genetic effects of selection, slowing resistance evolution if it occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The mathematical representation of the model is shown in Figure 1 b. In Lauenroth and Gokhale (2023), we presented a deterministic model of Johnsongrass' life cycle capturing all life-history stages and intraspecific competition between the plants, allowing the prediction of long-term population dynamics ( Figure 1 a). In the present study, we are interested in the probability and timing of herbicide resistance evolution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations